Assisted reproduction in patients with cardiac disease: A retrospective review. (September 2022) - Skorupskaite, Karolina; Joy, Eleanor; Balen, Adam; Agarwal, Kavita; Cauldwell, Matthew; English, Kate
Highlights: Data regarding the safety of assisted reproduction in patients with cardiac disease is scant. Increasing numbers of patients with known cardiac disease are seeking assisted reproduction. In most patients with cardiac disease assisted reproduction can be performed safely. Assisted reproduction in patients with cardiac disease requires a multi-disciplinary approach. Abstract: Objective: To assess risks of assisted reproduction in patients with cardiac disease. Study design: Retrospective case note review of patients with cardiac disease undergoing ART over a 10 year period in the obstetric cardiac services of three UK tertiary centres. Assessment of maternal, obstetric and fetal complications during ART and resultant pregnancies. Results: 34 patients with cardiac disease underwent 51 cycles of assisted reproduction. 24 patients (71%) received pre-pregnancy counselling. Mean age at the start of an assisted reproduction cycle was 32 years. Modified WHO (mWHO) risk category for the 34 patients was mWHO I, n = 3; mWHO II, n = 13; mWHO II- III, n = 10; mWHO III, n = 7; mWHO IV, n = 1. The 51 assisted reproduction cycles resulted in 31 pregnancies in 29 patients, and 31 live births, including two sets of twins. Live birth rate per cycle was 60.8%. Twin pregnancy rate per cycle was 5.8%. Four patients experienced complications during assisted reproduction treatment (7.8% per cycle); one major intra-abdominal haemorrhage following egg collection in a patient with a mechanical aortic valve, one endocarditis, one mild ovarian hyperstimulation syndrome and one vagal syncope during egg collection. Four other patients experienced cardiac complications during resultant pregnancies (12.9%). 43% of mWHO class III patients experienced cardiac, obstetric or neonatal complications. Five babies were delivered pre-term (<37/40). Conclusions: This small study demonstrates that assisted reproduction carries increased risks of complications in patients with cardiac disease, but can be undertaken without major complication in the majority, as long as appropriate adjustments to treatment pathways are made, and they are managed through a multi-disciplinary team.